2018
DOI: 10.1016/j.jspr.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A time-saving method for sealing Purdue Improved Crop Storage (PICS) bags

Abstract: Purdue Improved Crop Storage (PICS) bags were designed to reduce grain storage losses on smallholder farms. The bag consists of three layers: two high-density polyethylene liners fitted inside a woven polypropylene bag. Recently, farmer groups, development relief programs, and government food security agencies have shown interest in PICS bags for large-scale use. PICS bags are conventionally closed by a twist-tie (TT) method, which involves twisting, folding, and tying the lip of each layer individually with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…This happens when the infestation level is relatively high and when the ambient temperature is warmer. These conditions promote a more rapid rate of insect metabolism, and in some cases, respiration of the grain (Williams et al 2016, Kharel et al 2018). In addition, limited oxygen supply may affect insect behavior besides survivorship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This happens when the infestation level is relatively high and when the ambient temperature is warmer. These conditions promote a more rapid rate of insect metabolism, and in some cases, respiration of the grain (Williams et al 2016, Kharel et al 2018). In addition, limited oxygen supply may affect insect behavior besides survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic conditions are achieved mainly due to 1) respiration of insects and other organisms present including the grain itself and 2) making the storage system airtight to greatly restrict the movement of air from outside (Navarro et al 1994). Studies have shown that hermetic bagging systems such as Purdue Improved Crop Storage (PICS) bags can maintain oxygen levels at 2–15% for extended periods of time, typically for 3–6 mo, which limits insect population growth (Murdock et al 2012, Baoua et al 2014, Kharel et al 2018). Oxygen levels below 5% are effective in controlling various storage insects including Callosobruchus maculatus (Fabricius) (Coleoptera: Chrysomelidae), Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae), Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae), Oryzaephilus surinamensis (Linnaeus) (Coleoptera: Silvanidae), Sitophilus oryzae (Linnaeus) (Coleoptera: Curculionidae), S. zeamais Motschulsky (Coleoptera: Curculionidae), and Trogoderma granarium Everts (Coleoptera: Dermestidae) (Bailey 1965, Baributsa et al 2010, Murdock et al 2012, Baoua et al 2014, Martin et al 2015, Yan et al 2016, Kharel et al 2018).…”
mentioning
confidence: 99%
“…There are documented cases where oxygen levels increased under hermetic conditions after decreasing below 5%, likely due to unidentified breaches of the hermetic seals (Yan et al 2017, Kharel et al 2018). Despite the rise in oxygen, the quality of the stored grain and flour were maintained.…”
mentioning
confidence: 99%
“…The increase and the drop in relative humidity may also explain the decrease in moisture content of the maize grain in PP woven and ZeroFly ® bags after seven months of storage. As noted in previous studies, relative humidity and grain moisture content in the hermetic technologies are least affected by prevailing ambient conditions [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 78%